Puisi Pendidikan Solusi Penyelesaian Permasalahan Kedamaian di Patani Selatan Thai - Jehwae, Phaosan; Japakiya, Abdulfattah (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
This paper is the result of an investigation that aims to 1) synthesize social problems in Patani i.e., the three southern border regions of Thailand (known as Patani), 2) compose poems that reflect social problems, and 3) create youth responsibility for social problems in the southern border regions of Thailand. This research is quasi-experimental research. The instruments used in this research are 1) a synthetic form of social problems in the three southern border provinces of Thailand, 2) a contemporary Malay poet PUISI assessment form, and 3) a PUISIDRA competition rubric assessment model. The sample group used in the study was A total of 120 youths in the southern border provinces conducted self-data collection, there are 3 stages in the process, consisting of 1) pre-writing poetry, 2) poetry writing process, and 3) post-responsibility stage of social problems. The results showed that the synthesis of social problems in the three southern border provinces of Thailand into 10 problems, as follows: 1) education problem 2) security problem 3) violence problem 4) drug problem 5) adultery problem 6) technology problem 7) religion problem 8) filial piety problem 9) economic problem and 10) corruption problem. There are also poetry compositions reflecting social problems. The poems that have been written are 100 poems, which amount to 124 pages. Creation of youth responsibility for social problems in three southern border provinces of Thailand